Randomized clinical trial of BioFoam® Surgical Matrix to achieve hemostasis after liver resection. Issue 7 (July 2020) - Rahbari, Nuh N.; Birgin, Emrullah; Sturm, Dorothée; Schwanebeck, Uta; Weitz, Jürgen; Reissfelder, Christoph
Abstract: Background: Topical agents were designed to facilitate hemostasis during hepatic resection. The aim of this prospective randomized controlled clinical trial was to evaluate the effectiveness and safety of BioFoam® Surgical Matrix for achieving hemostasis after open hepatic resection. Methods: This was a prospective, randomized controlled monocentric trial of patients undergoing elective open liver resection between December 2015 and September 2017. The primary endpoint was time-to-complete hemostasis. Results: A total of 101 patients were enrolled in this trial, giving 51 patients in the BioFoam® group and 50 patients in the control group (without use of BioFoam®). Time-to-complete hemostasis was significantly reduced in the BioFoam® group (156 ± 129 versus 307 ± 264 s; P = 0.001). There were no significant differences in postoperative bile leaks (n = 6 (12%) vs. n = 5 (10%); P = 0.776), postoperative morbidity (n = 37 (73%) vs. n = 40 (80%); P = 0.482) or mortality (n = 3 (6%) vs. n = 1 (2%); P = 0.618) between groups. Conclusion: BioFoam® is a safe topical agent for achieving faster hemostasis during hepatic resection, however, the true clinical relevance of this finding needs to be further evaluated. ClinicalTrials.gov ID NCT02612220 .